Psychosocial Impact of Wheelchair Usage on Individuals with Mobility Disability in Ibadan, Nigeria (2015)
Background: Wheelchairs provide individuals with mobility impairments opportunity for independent living within their environment. However, using this device may have psychosocial impacts with consequent influence on the quality of life of the users. The psychosocial impact of wheelchair usage among individuals with mobility disability in a Nigerian community was investigated. Methods: The study is a descriptive cross-sectional survey. People who have been independent users of wheelchair for a minimum of six months prior to the study were recruited from centres for people with disabilities in Ibadan, Nigeria into the study. A profile of their use of the device was documented and the psychosocial impact of wheelchair was assessed using the Psychosocial Impact of Assistive Devices Scale. Data were analysed using descriptive and inferential statistics at p = 0.05. Results: Sixty consenting individuals with mobility disability participated in this study. Their mean age was 38.7±14.1 years. Majority (90%) were manual wheelchair users and two-thirds (63.3%) had been using the wheelchair for d” five years. Approximately a third of the participants use their wheelchairs occasionally. There was no significant difference (p=0.26) in the psychosocial impact of wheelchair usage between male and female users. Conclusion: The psychosocial impact of wheelchair was similar between male and female users. However, the impact was higher on the self-esteem of male than female users and lower on their competence than that of their female counterparts. This may be due to stigmatization or a culturally related unwillingness of men in our environment to be dependent on others.